Tales of Two Cities (Archaeopress Publishing, 2024)
Tales of Two Cities tells the story of Old Sarum and Salisbury, from the middle of the tenth century to the beginning of the twentieth. The volume brings together the most up-to-date thinking on the archaeological evidence for both medieval cities, and through analysis of the rich documentary record, charts the developments in the city settlements and their dependent suburbs. For the first time, the archaeological evidence for Old Sarum and its suburbs is brought together in synthesis to explore its rise in the eleventh century, its hey-day in the twelfth, and the rapid decline from the thirteenth century onwards. The ceramic, zooarchaeological and environmental evidence is assessed for both cities, alongside a comprehensive overview of the archaeological evidence for medieval Salisbury. How this new and visionary city took shape in the thirteenth century is analysed through chapters that examine its churches, its mills, its majestic marketplace and its innovative watercourses. Chapters on Old Sarum’s suburbs are matched by explorations of the medieval and later suburbs of Salisbury; Tales of Two Cities provides a fresh take on the story of this most illustrious cathedral city in the heart of southern England.